A LINGUISTIC AND CULTURAL ANALYSIS OF PUN EXPRESSIONS IN JOURNALISTIC ARTICLES IN JORDAN - Yousef Bader (European Scientific Journal, ESJ, 2014)
This study is a linguistic and cultural analysis of some pun expressions published recently in two Jordanian daily newspapers in Arabic. The study responds to calls by Delabatista (1997) and Ritchie (2004) to carry out studies on pun that deal with analysis of its practical uses rather dwell on categorization issues and theoretical backgrounds. The survey finds numerous cases of wordplay in these articles, some of which fall under the category of humor, but many, contrary to what was stated before, cannot be categorized under humor because they refer to recent bloody infighting in the Arab World, especially Syria, and they actually call for tears rather than laughter. Types of word play used include the homographic, homonymic, onomastic, and other types discussed in the literature. The new thing in this study is the case of playing on similarities between two words in taw different languages like Arabic and English to produce a respectable pun.